Leather-imitated superfine fiber layered synthetic leather and production process thereof
Through multi-layer structural design and process optimization, combined with fiber modification and surface treatment, the shortcomings of synthetic leather in terms of feel, breathability, texture and dyeing performance have been solved, achieving high simulation and stable production results.
Patent Information
- Application Number
- CN202610012536.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-07
- Publication Date
- 2026-02-06
AI Technical Summary
Existing synthetic leathers cannot match natural leather in terms of feel, breathability, texture, and dyeing performance, and their production processes are unstable, resulting in large fluctuations in performance.
Employing a multi-layered structural design, including a high-density fiber base layer, a fiber/resin composite reinforcement layer, a porous polyurethane surface layer, and a biomimetic texture layer, this synthetic leather utilizes a gradient fiber network, a two-component PU wet process, and a high-temperature embossing process, combined with fiber chemical modification and surface treatment, to create a synthetic leather with excellent comprehensive performance.
It achieves high simulation, soft feel, breathability and moisture permeability, and a realistic natural leather appearance, while improving mechanical properties and color fastness, solving the problems of insufficient performance and production instability of traditional synthetic leather.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of synthetic leather technology, and in particular to a simulated leather microfiber layered synthetic leather and its production process. Background Technology
[0002] Microfiber synthetic leather, as an important alternative to natural leather, has been widely used in footwear, bags, furniture, and automotive interiors due to its advantages in resource utilization, environmental friendliness, and performance uniformity. However, as consumers' demands for product quality and sensory experience continue to rise, existing technologies for producing simulated leather still have many shortcomings in overall performance and cannot fully match natural leather.
[0003] First, regarding the substrate structure, traditional synthetic leather often uses a uniform and dense non-woven fabric substrate. While this ensures a certain level of mechanical strength, it often results in a stiff feel, lacking the softness and fluffiness of natural leather, and exhibiting poor breathability and moisture permeability. Second, in terms of simulation effect, the textures created by conventional embossing processes are relatively shallow and rigid, lacking the three-dimensionality and realism of natural leather grain patterns, and the texture's durability is insufficient. Furthermore, for microfiber, a key raw material, its smooth surface and strong chemical inertness make dyeing difficult, generally resulting in low dye uptake and poor color fastness, limiting the product's color richness and quality stability.
[0004] In coating and lamination processes, most existing technologies use a single polyurethane (PU) slurry for impregnation or coating, making it difficult to simultaneously achieve deep bonding strength, surface feel, and breathability. Furthermore, insufficient interlayer bonding easily leads to delamination, and the hydrolysis and aging resistance of the surface resin needs improvement. From a production process perspective, existing methods have wide control ranges for parameters in each step, and the synergistic effects of each component are unclear, resulting in large fluctuations in product performance and making it difficult to achieve stable production of high-performance simulated leather.
[0005] Therefore, developing a layered synthetic leather and its preparation method that can comprehensively improve from fiber substrate modification and structural innovation to process optimization, and achieve high simulation, excellent comprehensive performance and stable production, has become an urgent technical problem to be solved in this field. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a simulated leather microfiber layered synthetic leather and its production process.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] A simulated leather microfiber layered synthetic leather, characterized by a multi-layered structure, comprising, from bottom to top, the following:
[0009] (1) High-density fiber base layer: It is composed of chemically modified ultrafine fibers, which are formed by air-flow web formation and differentiated needle punching process to form a gradient fiber web with a denser bottom layer and a sparser top layer. The bottom layer fibers are tightly arranged and have a high degree of entanglement, providing core mechanical support, tensile strength and dimensional stability for the product.
[0010] (2) Fiber / resin composite reinforcement layer: formed by impregnating and solidifying anionic waterborne polyurethane resin on the bottom layer of the above-mentioned fiber substrate. The anionic waterborne polyurethane resin contains uniformly dispersed ultrafine wood powder, which functions to strongly bond the fibers, enhance the overall structure, and may adjust the material density and feel, forming a solid intermediate transition layer.
[0011] (3) Porous polyurethane surface layer: It is formed by coating the surface of the fiber / resin composite reinforcement layer with soft hydrolysis resistant water-based polyurethane resin and then solidifying it by wet method. This layer has a dense surface and is rich in finger-shaped and honeycomb-shaped interconnected micropores. The thickness is about 0.2-0.4 mm, which directly determines the soft feel, breathability and moisture permeability of synthetic leather and the texture of the base layer.
[0012] (4) Bionic texture layer: Through high temperature and high pressure embossing process, the grain pattern of genuine leather is permanently imprinted on the porous polyurethane surface layer. The pattern depth is 400-800μm, giving the product a realistic natural leather visual appearance and three-dimensional touch.
[0013] (5) Multifunctional surface finishing layer: Through roller coating and baking, a transparent continuous protective film is formed on the surface of the biomimetic texture layer. This layer further endows the product with excellent waterproofness, wear resistance, and scratch resistance, and optimizes the surface feel. At the same time, it plays the role of fixing dyes and improving color fastness.
[0014] Preferably, the microfiber in (1) is a fixed island-island composite microfiber short fiber, the island component is polyethylene terephthalate, the sea component is alkali-soluble polyester, and the island-sea ratio is 70 / 30.
[0015] Preferably, the chemical modification in (1) is achieved by introducing methacryloyloxyethyltrimethylammonium chloride (DMC), hydroxyethyl methacrylate phosphate (HEMAP), and 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone (UV-1) monomers onto the fiber surface through a graft copolymerization reaction.
[0016] Preferably, the gradient fiber web in (1) is formed by airflow web formation and needle punching, wherein the needle punching density decreases gradually from the bottom layer to the surface layer, with the bottom layer having 350 needles / cm. 2 Middle layer 250 thorns / cm 2 150 thorns / cm on the surface 2 The needle punching frequency is 600-1000 punches / min, and the fiber web conveying speed is 2-10m / min.
[0017] Preferably, the anionic waterborne polyurethane resin in (2) is RL-8302 with a solid content of 30%, purchased from Guangzhou Ruilin New Materials Co., Ltd.
[0018] Preferably, the soft, hydrolysis-resistant waterborne polyurethane resin in (3) is model BW-8209 with a solid content of 35%, and was purchased from Zibo Baowei New Material Technology Co., Ltd.
[0019] A production process for simulated microfiber layered synthetic leather includes the following steps:
[0020] S1. Preparation of modified microfiber nonwoven fabric:
[0021] Prepare NaOH solutions with mass concentrations of 6-30 g / L at room temperature, treat the microfibers with a bath ratio of 1:20-50, at a temperature of 80-90℃ for 30-60 min, wash the treated microfibers with distilled water until the pH value of the microfiber adhering solution is around 6-7, and then dry them at 40℃.
[0022] Weigh out the following components sequentially: methacryloyloxyethyltrimethylammonium chloride (DMC), hydroxyethyl methacrylate phosphate (HEMAP), and 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone (UV-1) monomer, add them to deionized water to prepare an 8-14 wt% mixed solution. Stir for 5-15 min, add 2-5 g / L of penetrant fatty alcohol polyoxyethylene ether (JFC), stir for 3-5 min, slowly add potassium persulfate (KPS), stir for 10-20 min, add deionized water to bring the solid content of the mixed solution to 6-10 wt%, stir for 5-15 min, and obtain the mixed solution.
[0023] Using a liquor ratio of 1:20-50, the alkali-treated microfibers are introduced into the impregnation tank in a flat state, ensuring that the microfibers are completely immersed in the mixed solution. The impregnation time is 5-10 minutes. The impregnated microfibers are then passed through a pair of rollers on a roller press with a surface pressure of 0.2-0.4 MPa to remove excess solution, controlling the liquid retention rate of the microfibers to 80-90%. The microfibers after being squeezed are placed in a hot air dryer at 55-65℃ and reacted for 45-60 minutes. During this process, KPS decomposes upon heating to generate free radicals, initiating a graft copolymerization reaction of the three monomers on the surface of the microfibers. After the reaction, the microfibers are removed and washed countercurrently with warm water at 40-50℃ for 2-3 times in a continuous washing machine to thoroughly remove unreacted monomers, homopolymers, and residual additives. Finally, the microfibers are dried in a drying equipment at 90℃ to obtain the chemically modified microfiber nonwoven fabric. The reaction mechanism is as follows:
[0024] ;
[0025] S2. Forming of gradient fiber web nonwoven fabric:
[0026] The modified microfiber nonwoven fabric obtained from S1 is fed into an airflow web forming machine. By adjusting the airflow in the conveying pipeline to 12-25m / s, the suction negative pressure to 800-1500Pa, and the reciprocating speed of the web laying curtain to 5-15m / min, a gradient fiber web structure with a denser bottom layer and a sparser top layer is formed. This can be achieved by laying 4-8 layers, with the bottom layer using finer and shorter fibers to increase density. The formed gradient fiber web is then fed into a needle punching machine. The needles deeply penetrate the bottom layer to 8-15mm to strengthen entanglement, and shallowly penetrate the surface layer to 3-6mm to avoid damaging the bulk. After needle punching, a gradient fiber web nonwoven fabric with a certain strength, high bulk, and a through-hole three-dimensional network structure is formed.
[0027] 3. Two-component PU wet-process synthetic leather:
[0028] Component A: In a mixing tank, first add DMF solvent, then add wood powder with a mesh size of 400 or higher, and stir for 5-15 minutes to ensure full dispersion. Then, add anionic waterborne polyurethane resin, anionic surfactant OT-70, and nonionic surfactant S-80 in sequence. Stir at 1000-2000 rpm for 15-25 minutes, and finally degas under vacuum for 30-40 minutes. Filter with a 100-mesh filter for later use.
[0029] Component B: In a separate mixing tank, add DMF solvent, then add soft, hydrolysis-resistant waterborne polyurethane resin and 1-2% of porogen ammonium bicarbonate. Stir at 1000-2000 rpm for 15-25 min, then vacuum degas for 30-40 min. Filter with a 100-mesh filter for later use.
[0030] The gradient fiber web nonwoven fabric obtained from S2 is first wetted in a water tank and then rolled dry to a moisture content of approximately 30% to prevent excessive penetration of the sizing agent. Next, it is impregnated with component A sizing agent, with the liquid content controlled at 30-60% using a doctor blade to ensure the resin fully penetrates the bottom layer of the nonwoven fabric without excessive penetration to the surface. Immediately afterward, a 0.2-0.4 mm thick layer of component B sizing agent is evenly coated onto the surface of the impregnated nonwoven fabric using a precision doctor blade or roller coater. The coated nonwoven fabric is then immediately placed into a coagulation tank. The coagulation solution is a mixture of DMF and H2O, with the DMF concentration controlled at 20-25%. The temperature is controlled at 25-35℃. The nonwoven fabric stays in the coagulation liquid for 10-12 minutes. During this process, DMF and H2O undergo double diffusion, PU resin demulsifies and coagulates, and component B forms a dense surface and internally interconnected finger-like pores and honeycomb pore structure. Component A coagulates inside the nonwoven fabric to achieve strong adhesion. After complete coagulation, it enters a multi-compartment washing tank, and the water temperature is raised to 60℃. Through multiple rolling and washing, the DMF content in the nonwoven fabric is reduced to below 1%. Finally, it is dried in an oven at 100-120℃ for 12-24 hours to obtain the semi-finished product - wet synthetic leather.
[0031] S4. Replication and shaping of surface texture:
[0032] The S3 semi-finished synthetic leather is conditioned for 24 hours at a temperature of 55-65℃ and a humidity of 24-26% to ensure uniform moisture content and optimal plasticity. Using a through-type embossing machine, the leather is first passed through a 60℃ preheating roller and then into the heating zone at a temperature of 160-180℃. The embossing pressure is set to 0.35-0.7MPa through the gap between the embossing roller and the plaining roller, and the embossing time is about 5-10 seconds. The surface of the embossing roller is engraved with the grain pattern of the target genuine leather (such as calfskin), with a pattern depth of 400-800μm. After embossing, the leather is immediately cooled by water through a cooling roller to quickly set the pattern and prevent rebound.
[0033] S5. Staining and Post-treatment:
[0034] Place the S4 synthetic leather fabric into a dyeing machine, use cationic dyes, a liquor ratio of 1:15-20, adjust the pH value to 4-5.5, start dyeing at 40℃, and raise the temperature to 85-90℃ at a rate of 0.5-1℃ / min, and hold the dyeing temperature for 30-45 minutes. Since the fibers have been grafted with cationic sites, the dyeing is rapid and uniform. After dyeing, drain the water and wash with warm water. Apply the surface treatment solution to the texture of the dyed synthetic leather using a roller coating method, with a coating amount of 30-50g / m². Then bake in an oven at 95-130℃ for 2-3 minutes to form a transparent protective film. This layer further endows the product with waterproof, wear-resistant, scratch-resistant and improved hand feel. Set the surface-treated synthetic leather at 110-115℃ for 10-15 minutes to completely fix the dye and improve color fastness. Finally, after cooling, edge trimming, inspection and winding, the finished imitation leather microfiber layered synthetic leather is obtained.
[0035] Preferably, the mass ratio of the three monomers DMC, HEMAP, and UV-1 in S1 is 1:0.67-0.8:0.33-0.4.
[0036] Preferably, the amount of potassium persulfate used in S1 is 0.5-5% of the total mass of the monomer.
[0037] Preferably, in S3, the mass ratio of component A, anionic waterborne polyurethane resin RL-8302, to DMF is 1:0.5-1, the amount of wood powder is 5-10% of the mass of RL-8302 resin, the amount of anionic surfactant OT-70 is 0.5-1% of the mass of RL-8302 resin, and the amount of nonionic surfactant S-80 is 1-2% of the mass of RL-8302 resin.
[0038] Preferably, in S3, the amount of B component soft hydrolysis-resistant waterborne polyurethane resin BW-8209 is 30-50% of the mass of RL-8302 resin, the mass ratio of BW-8209 resin to DMF is 1:0.7-1.2, and the amount of pore-forming agent ammonium bicarbonate is 1-2% of the mass of BW-8209 resin.
[0039] Preferably, the cationic dye in S5 is at least one of cationic pale yellow 7GL, cationic yellow X-6G, cationic pink FG, cationic red CTL, cationic turquoise blue CB, and cationic blue FCL.
[0040] Preferably, the surface treatment liquid in S5 is of model YuPud@4858, purchased from Jingcheng New Materials Co., Ltd.
[0041] Compared with the prior art, the beneficial effects of the present invention are:
[0042] 1. Significant improvement in simulation and overall performance: Through the synergistic design of "gradient fiber base layer + two-component PU wet process + biomimetic embossing", the product achieves a high degree of simulation of natural leather in terms of mechanical properties, feel, breathability and appearance texture, overcoming the shortcomings of traditional synthetic leather such as stiff feel, poor breathability and dull texture.
[0043] 2. Functional Optimization Through Structural Innovation: The gradient fiber base layer, with its dense bottom layer providing high-strength support and a loose surface layer maintaining high bulk, forms a continuous three-dimensional network structure, giving the product excellent tensile strength, dimensional stability, and good cushioning resilience. The two-component PU layered design: Component A (containing wood powder) penetrates deep into the fiber interior for strong adhesion and reinforcement; Component B forms a dense surface and porous interior structure, ensuring the surface layer's softness, breathability, and hydrolysis resistance. The two components have clear divisions of labor and work synergistically.
[0044] 3. Fundamental improvements brought about by chemical modification of the base fiber: Through alkali treatment and graft copolymerization of DMC / HEMAP / UV-1 monomers, the fiber is endowed with the following characteristics: permanent cationic sites (DMC), which allows for subsequent dyeing with cationic dyes with high dyeing rate and good color fastness, solving the problems of difficult dyeing and poor color fastness of microfiber; phosphate ester groups (HEMAP), which enhance the interfacial bonding force between the fiber and anionic PU resin and improve the interlayer peel strength; and ultraviolet absorption structure (UV-1), which improves the product's resistance to ultraviolet aging and extends its service life. Detailed Implementation
[0045] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0046] Example 1: A production process for simulated leather microfiber layered synthetic leather, comprising the following steps:
[0047] S1. Preparation of modified microfiber nonwoven fabric:
[0048] Prepare a 15 g / L NaOH solution with a bath ratio of 1:30. Immerse 100 parts of island-shaped microfiber short fibers in the solution and treat at 85℃ for 45 min. After treatment, wash with distilled water until pH=6.5 and dry at 40℃. Add 1.0 part of DMC, 0.7 parts of HEMAP, and 0.35 parts of UV-1 to deionized water to prepare a 10 wt% mixture. Add 3 g / L JFC penetrant and stir. Add 1% of KPS initiator by the total mass of monomers and add water to bring the solid content to 8%. Immerse the alkali-treated fibers in the above mixture with a bath ratio of 1:30 for 8 min. Roll the fibers through a 0.3 MPa roller with a liquid retention rate of 85%. Place the fibers in a 60℃ hot air drying tunnel and react for 50 min. Wash the fibers three times with 45℃ warm water in a countercurrent manner and dry at 90℃ to obtain chemically modified microfiber nonwoven fabric.
[0049] S2. Forming of gradient fiber web nonwoven fabric:
[0050] The fibers obtained from S1 are fed into an air-laid web forming machine with an airflow velocity of 18 m / s, a suction negative pressure of 1200 Pa, and a web laying speed of 8 m / min. Six layers are laid to form a gradient fiber web, which is then fed into a needle punching machine. The needle punching depth of the bottom layer is 12 mm (density 350 needles / cm). 2 ), middle layer 8mm (250 thorns / cm) 2 ), surface layer 4mm (150 thorns / cm) 2 The needle puncture frequency is 800 punctures / min, and the delivery speed is 5m / min.
[0051] S3, Two-component PU wet-process synthetic leather:
[0052] Preparation of component A: Add 80 parts DMF and 8 parts 400-mesh wood powder to a mixing tank and disperse for 10 min. Then add 100 parts RL-8302 resin, 0.8 parts OT-70, and 1.5 parts S-80 in sequence. Stir at 1500 rpm for 20 min, degas under vacuum for 35 min, and filter through a 100-mesh filter.
[0053] Preparation of component B: Add 40 parts DMF, 40 parts BW-8209 resin, and 0.6 parts ammonium bicarbonate to another tank, stir at 1500 rpm for 20 min, degas under vacuum for 35 min, and filter through a 100 mesh filter;
[0054] The gradient fiber web obtained from S2 was wetted and rolled dry to a moisture content of 30%, then impregnated with component A slurry. The liquid content was controlled at 45% by a scraper. Then, component B slurry was rolled onto its surface to form a wet film thickness of 0.3 mm. The web was immediately placed in a coagulation tank (DMF concentration 22%, temperature 30℃) and held for 11 min. It was then washed in a multi-cell countercurrent washing process with 60℃ warm water until the DMF residue was <1%. Finally, it was dried in an oven at 110℃ for 18 h to obtain a semi-finished product.
[0055] S4. Replication and shaping of surface texture:
[0056] The S3 semi-finished product was conditioned at 60℃ and 25%RH for 24 hours. After passing through a 60℃ preheated roller, it entered the embossing machine. The embossing temperature was 170℃, the pressure was 0.5MPa, and the time was 8s (using a 600μm deep calfskin grain pattern roller). After embossing, it was immediately water-cooled for shaping.
[0057] S5. Staining and Post-treatment:
[0058] Place the S4 synthetic leather fabric into a dyeing machine with a liquor ratio of 1:18. Adjust the pH to 4.5 with acetic acid, add cationic red CTL dye, and start dyeing at 40℃. Increase the temperature to 88℃ at a rate of 0.8℃ / min, and maintain the dyeing temperature for 40 minutes. Drain the fabric, wash with warm water, and roll-coat with YuPud@4858 treatment solution at a coating weight of 40 g / m². 2 The product is baked in an oven at 120℃ for 2.5 minutes, then set at 113℃ for 12 minutes, cooled, inspected, and rolled up to obtain the finished simulated leather microfiber layered synthetic leather.
[0059] Example 2: A production process for simulated leather microfiber layered synthetic leather, comprising the following steps:
[0060] S1. Preparation of modified microfiber nonwoven fabric:
[0061] Prepare a 15 g / L NaOH solution with a bath ratio of 1:30. Immerse 100 parts of island-shaped microfiber short fibers in the solution and treat at 85℃ for 45 min. After treatment, wash with distilled water until pH=6.5 and dry at 40℃. Add 1.0 part of DMC, 0.7 parts of HEMAP, and 0.35 parts of UV-1 to deionized water to prepare a 10 wt% mixture. Add 3 g / L JFC penetrant and stir. Add 1% of KPS initiator by the total mass of monomers and add water to bring the solid content to 8%. Immerse the alkali-treated fibers in the above mixture with a bath ratio of 1:30 for 8 min. Roll the fibers through a 0.3 MPa roller with a liquid retention rate of 85%. Place the fibers in a 60℃ hot air drying tunnel and react for 50 min. Wash the fibers three times with 45℃ warm water in a countercurrent manner and dry at 90℃ to obtain chemically modified microfiber nonwoven fabric.
[0062] S2. Forming of gradient fiber web nonwoven fabric:
[0063] The fibers obtained from S1 are fed into an air-laid web forming machine with an airflow velocity of 18 m / s, a suction negative pressure of 1200 Pa, and a web laying speed of 8 m / min. Six layers are laid to form a gradient fiber web, which is then fed into a needle punching machine. The needle punching depth of the bottom layer is 12 mm (density 350 needles / cm). 2 ), middle layer 8mm (250 thorns / cm) 2 ), surface layer 4mm (150 thorns / cm) 2 The needle puncture frequency is 800 punctures / min, and the delivery speed is 5m / min.
[0064] S3, Two-component PU wet-process synthetic leather:
[0065] Preparation of component A: Add 70 parts DMF and 6 parts 400-mesh wood powder to a mixing tank and disperse for 10 min. Then add 100 parts RL-8302 resin, 0.7 parts OT-70, and 1.2 parts S-80 in sequence. Stir at 1500 rpm for 20 min, degas under vacuum for 35 min, and filter through a 100-mesh filter.
[0066] Preparation of component B: Add 35 parts DMF, 35 parts BW-8209 resin, and 0.5 parts ammonium bicarbonate to another tank, stir at 1500 rpm for 20 min, degas under vacuum for 35 min, and filter through a 100 mesh filter;
[0067] The gradient fiber web obtained from S2 was wetted and rolled dry to a moisture content of 30%, then impregnated with component A slurry. The liquid content was controlled at 40% by a scraper. Then, component B slurry was rolled onto its surface to form a wet film thickness of 0.25 mm. The web was immediately placed in a coagulation tank (DMF concentration 20%, temperature 28℃) and left for 10 minutes. Then, it was washed in a multi-cell countercurrent washing process with 60℃ warm water until the DMF residue was <1%. Finally, it was dried in an oven at 110℃ for 18 hours to obtain a semi-finished product.
[0068] S4. Replication and shaping of surface texture:
[0069] The S3 semi-finished product was conditioned at 60℃ and 25%RH for 24 hours. After passing through a 60℃ preheated roller, it entered the embossing machine. The embossing temperature was 165℃, the pressure was 0.45MPa, and the time was 7s (using a 500μm deep calfskin grain pattern roller). After embossing, it was immediately water-cooled for shaping.
[0070] S5. Staining and Post-treatment:
[0071] Place the S4 synthetic leather fabric into a dyeing machine with a liquor ratio of 1:18. Adjust the pH to 5.0 with acetic acid, add cationic red CTL dye, and start dyeing at 40℃. Increase the temperature to 90℃ at a rate of 1℃ / min, and maintain the dyeing temperature for 35 minutes. Drain the fabric, wash with warm water, and roll-coat with YuPud@4858 treatment solution at a coating weight of 35 g / m². 2 The product is baked in an oven at 115℃ for 3 minutes, then shaped at 113℃ for 12 minutes, cooled, inspected, and rolled up to obtain the finished simulated leather microfiber layered synthetic leather.
[0072] Example 3: A production process for simulated leather microfiber layered synthetic leather, comprising the following steps:
[0073] S1. Preparation of modified microfiber nonwoven fabric:
[0074] Prepare a 10 g / L NaOH solution with a liquor ratio of 1:40. Immerse 100 parts of island-shaped microfiber short fibers in the solution and treat at 82℃ for 50 min. After treatment, wash with distilled water until pH=6.5 and dry at 40℃. Add 1.0 part of DMC, 0.8 parts of HEMAP, and 0.4 parts of UV-1 to deionized water to prepare a 7 wt% mixture. Add 3 g / L JFC penetrant and stir. Add 1.5% of KPS initiator by total monomer mass and add water to bring the solid content to 8%. Immerse the alkali-treated fibers in the above mixture with a liquor ratio of 1:40 for 9 min. Roll the fibers through a 0.3 MPa roller with a liquid retention rate of 82%. Place the fibers in a 58℃ hot air drying tunnel and react for 55 min. Wash the fibers three times with 45℃ warm water in a countercurrent manner and dry at 90℃ to obtain chemically modified microfiber nonwoven fabric.
[0075] S2. Forming of gradient fiber web nonwoven fabric:
[0076] The fibers obtained from S1 are fed into an air-laid web forming machine with an airflow velocity of 15 m / s, a suction negative pressure of 1400 Pa, and a web laying speed of 6 m / min. Seven layers are laid to form a gradient fiber web, which is then fed into a needle punching machine. The bottom layer is needle punched to a depth of 14 mm (density 350 needles / cm). 2 ), middle layer 9mm (250 thorns / cm) 2 ), surface layer 5mm (150 thorns / cm) 2 The needle puncture frequency is 800 punctures / min, and the delivery speed is 5m / min.
[0077] S3, Two-component PU wet-process synthetic leather:
[0078] Preparation of component A: Add 90 parts DMF and 8 parts 400-mesh wood powder to a mixing tank and disperse for 10 min. Then add 100 parts RL-8302 resin, 1.0 part OT-70, and 2.0 parts S-80 in sequence. Stir at 1500 rpm for 20 min, degas under vacuum for 35 min, and filter through a 100-mesh filter.
[0079] Preparation of component B: Add 50 parts DMF, 45 parts BW-8209 resin, and 0.8 parts ammonium bicarbonate to another tank, stir at 1500 rpm for 20 min, degas under vacuum for 35 min, and filter through a 100 mesh filter;
[0080] The gradient fiber web obtained from S2 was wetted and rolled dry to a moisture content of 30%, then impregnated with component A slurry. The liquid content was controlled at 55% by a scraper. Then, component B slurry was rolled onto its surface to form a wet film thickness of 0.35 mm. The web was immediately placed in a coagulation tank (DMF concentration 24%, temperature 32℃) and held for 11.5 min. It was then washed in a multi-cell countercurrent washing process with 60℃ warm water until the DMF residue was <1%. Finally, it was dried in an oven at 110℃ for 18 h to obtain a semi-finished product.
[0081] S4. Replication and shaping of surface texture:
[0082] The S3 semi-finished product was conditioned at 60℃ and 25%RH for 24 hours. After passing through a 60℃ preheated roller, it entered the embossing machine. The embossing temperature was 175℃, the pressure was 0.6MPa, and the time was 9s (using a 700μm deep calfskin grain pattern roller). After embossing, it was immediately water-cooled for shaping.
[0083] S5. Staining and Post-treatment:
[0084] Place the S4 synthetic leather fabric into a dyeing machine with a liquor ratio of 1:18. Adjust the pH to 4.5 with acetic acid, add cationic red CTL dye, and start dyeing at 40℃. Increase the temperature to 86℃ at a rate of 0.6℃ / min, and maintain the dyeing temperature for 45 minutes. Drain the fabric, wash with warm water, and roll-coat with YuPud@4858 treatment solution at a coating weight of 45 g / m². 2 The product is baked in an oven at 125℃ for 2 minutes, then set at 113℃ for 12 minutes, cooled, inspected, and rolled up to obtain the finished simulated leather microfiber layered synthetic leather.
[0085] Comparative Example 1: Based on Example 1, the difference is that the graft copolymerization modification in step S1 is completely omitted, the fiber is only treated with alkali, washed and dried and then directly enters S2, the rest is the same as Example 1.
[0086] Comparative Example 2: Based on Example 1, the difference is that in step S2, gradient needling is eliminated, and a uniform needling process is adopted, with a uniform needling density of 250 needles / cm² across the entire layer. 2 The needle puncture depth was 8 mm, and the rest was the same as in Example 1.
[0087] Comparative Example 3: Based on Example 1, the difference is that no ultrafine wood powder is added when preparing component A in step S3, and the rest of the formulation and process are the same as in Example 1.
[0088] Comparative Example 4: Based on Example 1, the difference is that in step S3, instead of using the two-component system of A and B, a single slurry is prepared: 100 parts of RL-8302 resin, 120 parts of DMF, 8 parts of wood powder, 0.8 parts of OT-70, 1.5 parts of S-80, and 0.6 parts of ammonium bicarbonate. The fiber web is impregnated and coated with this single slurry, and the rest is the same as in Example 1.
[0089] Comparative Example 5: Based on Example 1, the difference is that the surface treatment (roller coating of YuPud@4858 and baking) in step S5 is completely omitted, and only high-temperature setting is performed after dyeing. The rest is the same as in Example 1.
[0090] Performance testing:
[0091] 1. Mechanical property testing: The synthetic leather samples prepared in Examples 1-3 and Comparative Examples 1-5 were tested on an Instron 3345 universal testing machine according to GB / T 3916-2013 "Determination of breaking strength and elongation at break of single yarn in packaged textiles (CRE method)". The clamping distance was 25 mm, the tensile speed was 10 mm / min, and the test was conducted under standard temperature and humidity conditions. The tensile strength and elongation at break of the sample were recorded. Each sample was tested 20 times and the average value was taken. The experimental results are shown in Table 1.
[0092] 2. Moisture permeability test: The synthetic leather samples prepared in Examples 1-3 and Comparative Examples 1-5 were tested using a YG601H computer-controlled fabric moisture permeability meter, according to GB / T 12704.2-2009 "Textiles - Test Methods for Moisture Permeability of Fabrics - Part 2: Evaporation Method". The evaporation method was used, with a test condition of 38℃ and 90% relative humidity. Distilled water was placed in the permeability cup, and the effective test area of the sample was 33.0 cm². 2 Place the sealed permeation cup into a constant temperature and humidity chamber, and begin testing after equilibration for 1 hour. Weigh the cup every hour to measure the mass change, and continue testing for 6 hours. Calculate the permeability (g / m²) based on the water vapor permeation rate per unit area per unit time. 2 • 24h), each sample was tested 5 times and the average value was taken. The experimental results are shown in Table 1.
[0093] 3. Air permeability test: The synthetic leather samples prepared in Examples 1-3 and Comparative Examples 1-5 were tested using an air permeability tester according to QB / T 5156-2017 "Test Methods for Air Permeability of Artificial Leather and Synthetic Leather". A test head with a 20cm² area was selected. 2 The test pressure difference was set to 100 Pa. The sample was flat and clamped on the test head. The instrument automatically measured the volume of airflow passing vertically through a unit area of the sample per unit time under the specified pressure difference. The result was expressed as air permeability (mm / s). Each sample was tested 10 times at different locations and the average value was taken. The experimental results are shown in Table 1.
[0094] 4. Folding fastness test: The synthetic leather samples prepared in Examples 1-3 and Comparative Examples 1-5 were cut into strips according to the standard QB / T 2714-2018 "Determination of folding fastness of leather physical and mechanical tests". The samples were placed in test environments of -20℃ (low temperature) and 23℃ (normal temperature) for 4 hours respectively. Then the samples were clamped on the testing machine and bent repeatedly at a folding angle of 90° and a frequency of 100 times / min. The number of bends when cracks, pilling or coating peeling appeared on the sample surface was recorded. Each sample was tested 3 times and the average value was taken. The experimental results are shown in Table 1.
[0095] 5. Surface abrasion resistance test: The synthetic leather samples prepared in Examples 1-3 and Comparative Examples 1-5 were tested on a Martindale abrasion tester in accordance with GB / T21196.2-2007 "Textiles - Martindale Method - Determination of Abrasion Resistance of Fabrics - Part 2: Determination of Specimen Breakage". Standard wool felt was used as the friction material. A load of 1 kg was applied to the sample and rubbed at a frequency of 50 rpm. The test was continued until obvious wear, holes or coating peeling appeared on the sample surface. The number of rubs at this time was recorded. Each sample was tested 3 times and the average value was taken. The experimental results are shown in Table 1.
[0096] 6. Hydrolysis Resistance Test: The synthetic leather samples prepared in Examples 1-3 and Comparative Examples 1-5 were tested in a constant temperature and humidity aging chamber according to the standard QB / T 4671-2014 "Test Methods for Hydrolysis Resistance of Artificial Leather". The samples were suspended in the chamber and the environmental conditions were set to 70℃ and 95%RH. After aging for 7 consecutive days, the samples were taken out and adjusted to the standard temperature and humidity environment for 24 hours. The appearance changes of the samples before and after aging (such as stickiness, bubbling, discoloration, powdering, etc.) were compared. Each sample was tested 3 times and the average value was taken. The experimental results are shown in Table 1.
[0097] 7. Yellowing Resistance Test: The synthetic leather samples prepared in Examples 1-3 and Comparative Examples 1-5 were tested in a UV lamp-type yellowing resistance test chamber according to the standard QB / T 4672-2014 "Test Methods for Yellowing Resistance of Artificial Leather and Synthetic Leather". The samples were cut into rectangles of not less than 70mm × 40mm and placed flat on the sample rack of the test chamber. A UV-A band ultraviolet light source that meets the standard requirements (such as a fluorescent ultraviolet lamp with a main wavelength of 365nm) was used. The distance from the sample surface to the lamp tube was adjusted to 250mm ± 2mm. The temperature inside the chamber was controlled at 50℃ ± 2℃. After continuous irradiation for 24 hours, the samples were taken out. Under a standard light source box (such as a D65 light source), the color difference between the irradiated area and the unirradiated area of the sample was measured using a colorimeter. The color difference value ΔE was calculated according to the CIELAB color space. Three different parts of each sample were tested and the average value was taken. The experimental results are shown in Table 1.
[0098] 8. Dry / Wet Rubbing Fastness Test: The synthetic leather samples prepared in Examples 1-3 and Comparative Examples 1-5 were tested on a Y571B rubbing fastness tester according to GB / T 3920-2008 "Textiles - Tests for Color Fastness - Color Fastness to Rubbing". Dry and wet rubbing tests were performed separately. For dry rubbing: a standard dry rubbing cloth was wrapped around the rubbing head, and a vertical pressure of 9N ± 0.2N was applied to the sample, rubbing for 10 cycles at a reciprocating speed of 1 revolution per second. For wet rubbing: the rubbing cloth was soaked in distilled water to achieve a moisture content of 95%-100%, and then rubbing for 10 cycles was performed. After rubbing, the rubbing cloth was removed and air-dried at room temperature. The dried rubbing cloth was then compared with GB / T 3920-2008. The staining grade of the rubbing cloth was evaluated by comparing it with the gray scale card for assessing staining in textiles according to 251-2008 "Tests for Color Fastness of Textiles". The color fastness to dry rubbing and color fastness to wet rubbing were evaluated separately, and the results were expressed as grades 1-5 (grade 5 is the best and grade 1 is the worst). Each sample was tested three times for dry rubbing and three times for wet rubbing, and the average value was taken. The experimental results are shown in Table 1.
[0099] 9. Static water absorption rate test: The synthetic leather samples prepared in Examples 1-3 and Comparative Examples 1-5 were cut into 10cm×10cm squares according to GB / T4745-2012 "Test and Evaluation of Waterproof Performance of Textiles - Water Immersion Method". After conditioning in a standard temperature and humidity environment for 24 hours, the dry weight (m0) was weighed using an electronic balance (accuracy 0.001g). Then, the sample was completely immersed in a container filled with distilled water and left to soak at room temperature for 24 hours. The sample was then removed and hung vertically to drain for 2 minutes until no continuous water droplets fell. The wet weight (m1) was then weighed immediately. The static water absorption rate (W) was calculated using the following formula: W (%) = [(m1-m0) / m0] ×100%. Each sample was tested 5 times and the average value was taken. The experimental results are shown in Table 1.
[0100] Table 1. Performance Test Results
[0101]
[0102] Data Analysis:
[0103] 1. Mechanical property analysis (tensile strength, elongation at break):
[0104] The tensile strength (11.5-13.2 MPa) and elongation at break (85%-110%) of Examples 1-3 are excellent and balanced, indicating that the products have both high strength and good toughness through the complete process of the present invention. The highest tensile strength (13.2 MPa) was obtained in Example 3 by optimizing fiber modification (such as increasing the HEMAP ratio) and needle punching density.
[0105] Comparative Example 1 (without fiber chemical modification): Tensile strength (8.1 MPa) and elongation at break (65%) both decreased significantly, proving that graft copolymerization on the fiber surface is crucial for enhancing the fiber itself and its interfacial bonding with PU resin, and is the basis for improving the mechanical properties of the matrix.
[0106] Comparative Example 2 (without gradient structure) and Comparative Example 4 (single-component PU): Their mechanical properties are also poor, indicating that the optimized stress distribution provided by the gradient fiber network and the efficient bonding and tough surface layer achieved by the two-component PU make important contributions to the overall mechanical properties.
[0107] 2. Comfort Analysis (Moisture Permeability, Air Permeability):
[0108] Moisture permeability of Examples 1-3 (3420-3950 g / m³) 2 Both the air permeability (24h) and air permeability (7.8-9.2 mm / s) are at a high level, far exceeding that of traditional synthetic leather. This is directly due to the synergistic effect of the internal through-porous structure formed by component B and the loose surface of the gradient fiber network.
[0109] All comparative examples showed a significant decline in moisture permeability and air permeability, especially Comparative Example 4 (single-component PU), which had the lowest air permeability (2.0 mm / s). This proves that the lack of component B, which is dedicated to forming a porous surface layer, is the main reason for the poor air permeability. Comparative Example 2 (without gradient structure) also severely hindered the passage of gas and liquid due to the overall density of the substrate.
[0110] 3. Durability analysis (flexural strength, surface abrasion resistance, hydrolysis resistance):
[0111] Examples 1-3 exhibited excellent durability, with flexural strength exceeding 90,000 cycles. Examples 1 and 3 even exceeded 100,000 cycles without cracking, indicating that the product structure can withstand long-term dynamic stress. The surface abrasion resistance (8,000-9,500 revolutions) and hydrolysis resistance (strength retention rate >92%) are excellent. This is due to the reinforcing effect of component A (containing wood powder), the hydrolysis resistance of component B resin, and the protection of the surface finishing layer (YuPud@4858).
[0112] Comparative Example 3 (component A without wood flour) and Comparative Example 5 (without surface finishing layer) showed the worst performance in terms of flexural and abrasion resistance, confirming the reinforcing effect of wood flour and the crucial role of the surface protective film in improving durability. Comparative Example 4 (single-component PU) had the worst hydrolysis resistance (60% strength retention), indicating that its resin system could not simultaneously achieve both adhesion and hydrolysis resistance.
[0113] 4. Appearance stability analysis (resistance to yellowing, color fastness):
[0114] Examples 1-3 show low yellowing resistance (ΔE 1.9-2.3) and high color fastness to dry / wet rubbing (dry rubbing grade 4-5, wet rubbing grade 4). This directly proves that the UV-1 monomer grafted onto the fiber effectively plays an anti-ultraviolet aging role, while the strong binding force between the cationic dye and the dyeing sites introduced by the DMC monomer on the fiber ensures high color fastness.
[0115] Comparative Example 1 (without fiber chemical modification) and Comparative Example 5 (without surface finishing layer) performed significantly worse in these items. Comparative Example 1 showed poor color fastness, proving that fiber modification is a prerequisite for achieving excellent dyeing performance; Comparative Example 5 also showed a decrease in color fastness, indicating that the surface finishing layer has a positive effect on fixing the dye.
[0116] 5. Surface characteristic analysis (static water absorption rate):
[0117] The static water absorption rate (13-18%) of Examples 1-3 is moderate, indicating that the product has a certain degree of hydrophilicity but does not absorb moisture excessively. This is related to the waterproof treatment of the surface finishing layer and the balanced design of the porous structure.
[0118] The static water absorption rates of Comparative Examples 1, 3, 4, and 5 were significantly higher (32-40%), indicating that when fiber modification, a reasonable resin composite layer, or a surface protective layer is lacking, the material is more easily wetted by water, which is not conducive to maintaining dimensional stability and cleanliness during daily use.
[0119] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A simulated leather microfiber layered synthetic leather, which has a multi-layered structure, characterized in that, Including those compounded sequentially from bottom to top: (1) High-density fiber base layer: It is composed of chemically modified ultrafine fibers, which are formed by airflow web formation and differentiated needle punching process to form a gradient fiber web with a denser bottom layer and a sparser top layer; (2) Fiber / resin composite reinforcement layer: formed by impregnation and solidification of anionic waterborne polyurethane resin in the bottom layer of the fiber substrate, wherein ultrafine wood powder is uniformly dispersed in the anionic waterborne polyurethane resin. (3) Porous polyurethane surface layer: The fiber / resin composite reinforcement layer is coated with soft hydrolysis resistant waterborne polyurethane resin and formed by wet solidification. The layer has a dense surface and a structure rich in finger-shaped and honeycomb-shaped interconnected micropores. (4) Bionic texture layer: The grain pattern of genuine leather is permanently imprinted on the porous polyurethane surface layer through a high temperature and high pressure embossing process; (5) Multifunctional surface finishing layer: A transparent, continuous protective film is formed on the surface of the biomimetic texture layer by roller coating and baking.
2. The simulated leather microfiber layered synthetic leather according to claim 1, characterized in that, The microfiber in (1) is a fixed island-island composite microfiber short fiber, the island component is polyethylene terephthalate, the sea component is alkali-soluble polyester, and the island-sea ratio is 70 / 30.
3. The simulated leather microfiber layered synthetic leather according to claim 1, characterized in that, The chemical modification in (1) is achieved by introducing methacryloyloxyethyltrimethylammonium chloride, hydroxyethyl methacrylate phosphate and 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone monomers onto the fiber surface through a graft copolymerization reaction.
4. The simulated leather microfiber layered synthetic leather according to claim 1, characterized in that, The gradient fiber web in (1) is formed by airflow web formation and needle punching, wherein the needle punching density decreases gradually from the bottom layer to the surface layer, with the bottom layer having 350 needles / cm. 2 Middle layer 250 thorns / cm 2 150 thorns / cm on the surface 2 The needle punching frequency is 600-1000 punches / min, and the fiber web conveying speed is 2-10m / min.
5. The simulated leather microfiber layered synthetic leather according to claim 1, characterized in that, The anionic waterborne polyurethane resin in (2) is model RL-8302 with a solid content of 30%; the soft hydrolysis-resistant waterborne polyurethane resin in (3) is model BW-8209 with a solid content of 35%.
6. A production process for a simulated leather microfiber layered synthetic leather as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Preparation of modified microfiber nonwoven fabric: Microfiber is treated with alkali, washed, and dried; a mixture containing methacryloyloxyethyltrimethylammonium chloride, hydroxyethyl methacrylate phosphate, and 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone monomer is prepared, and potassium persulfate is added as an initiator; the alkali-treated fiber is immersed in the mixture, rolled, and dried to initiate a graft copolymerization reaction; after the reaction, it is washed and dried to obtain chemically modified microfiber nonwoven fabric; S2. Forming of gradient fiber web nonwoven fabric: The nonwoven fabric obtained in S1 is formed into a gradient structure with a dense bottom layer and a sparse top layer by airflow web formation, and then reinforced by needle punching to obtain gradient fiber web nonwoven fabric. S3, Two-component PU wet synthetic leather: Prepare component A slurry and component B slurry; after wetting the gradient fiber web nonwoven fabric obtained in S2, first impregnate it with component A slurry, then coat it with component B slurry, and then put it into the coagulation liquid for wet coagulation, then wash it with water and dry it to obtain semi-finished wet synthetic leather. S4. Replication and shaping of surface texture: After conditioning the semi-finished product obtained in S3, preheat it, emboss it under high temperature and high pressure, and then cool and shape it after embossing. S5. Dyeing and post-treatment: The greige fabric obtained in S4 is dyed with cationic dyes, then surface treated, baked, and high-temperature set, and finally post-treated to obtain the finished product.
7. The production process of a simulated leather microfiber layered synthetic leather according to claim 6, characterized in that, The mass ratio of the three monomers in S1—methacryloyloxyethyltrimethylammonium chloride, hydroxyethyl methacrylate phosphate, and 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone—is 1:0.67-0.8:0.33-0.4; the amount of potassium persulfate used is 0.5-5% of the total mass of the monomers.
8. The production process of a simulated leather microfiber layered synthetic leather according to claim 6, characterized in that, The S3 component A slurry comprises anionic waterborne polyurethane resin RL-8302, DMF solvent, ultrafine wood powder, anionic surfactant OT-70, and nonionic surfactant S-80; wherein, the mass ratio of RL-8302 resin to DMF is 1:0.5-1, the amount of wood powder is 5-10% of the mass of RL-8302 resin, the amount of anionic surfactant OT-70 is 0.5-1% of the mass of RL-8302 resin, and the amount of nonionic surfactant S-80 is 1-2% of the mass of RL-8302 resin.
9. The production process of a simulated leather microfiber layered synthetic leather according to claim 6, characterized in that, The B component slurry in S3 comprises a soft, hydrolysis-resistant waterborne polyurethane resin BW-8209, DMF solvent, and ammonium bicarbonate pore-forming agent; wherein, the amount of BW-8209 is 30-50% of the mass of RL-8302 resin, the mass ratio of BW-8209 to DMF is 1:0.7-1.2, and the amount of ammonium bicarbonate is 1-2% of the mass of BW-8209 resin.
10. The production process of a simulated leather microfiber layered synthetic leather according to claim 6, characterized in that, The cationic dye in S5 is selected from at least one of cationic pale yellow 7GL, cationic yellow X-6G, cationic peach pink FG, cationic red CTL, cationic turquoise blue CB, and cationic blue FCL; the surface treatment uses a surface treatment liquid with the model number YuPud@4858.
Citation Information
Patent Citations
Leather-imitated thin-fold-line superfine synthetic leather and preparation method thereof
CN102774098A
Preparation method for seamless bonding polyurethane synthetic leather
CN103485192A
Waterborne polyurethane suede microfiber leather and preparation method thereof
CN115852702A
Same-color dyeing method for cotton-containing blended fabric
CN117822332A
High-adhesion weather-resistant water-based ink and preparation process thereof
CN121227114A
Cited By
Preparation method of lignin-based multidimensional interpenetrating network modified wood powder and application of lignin-based multidimensional interpenetrating network modified wood powder in synthetic leather
CN122037602A